A internacionalização de empresas familiares: um estudo do ciclo evolutivo e o processo de internacionalização - Leite, Ivani Tristan Morato (2007)
Economic interdependence between countries, together with increased international flows of goods and services, leads companies to compete in a globalized market. There has been an increased need for investment in other countries, to maintain competitiveness. The point of reference has shifted from the domestic to international markets. Brazil, irrespective of the relevant privatization processes of the 1990s, still has a timid participation in this scenario, and faces the challenge of becoming a country of transnational companies. At the same time, family businesses have a relevant weight in the national economy, and lead the economy of the western market, where entrepreneurial initiatives are strongly encouraged. The research that originated this dissertation had, as its main goal, the understanding of the interference of specific aspects of family businesses in the process of internationalization. The hypothesis raised was that they would have more difficulty in initiating the process of internationalization due to family conflicts, which interfere in the company: issues of succession or professionalization. Therefore, it has analyzed the interdependencies between the evolving cycle of the family business and the process of internationalization. This research project initiated with a conceptual inquiry into the themes that support this study: family business and internationalization. The theoretical principles related to the concept of family business and the particularities of its evolving cycle were tackled, considering the dimensions of the family, the company and ownership. In relation to internationalization, the following issues were explored: the different theoretical currents about internationalization, the process of internationalization in the Brazilian context, and in family businesses. With this exploratory research as a starting point, a case study was then carried out, with the objective of investigating the phenomenon of internationalization of a family business, considering its external and internal factors. In its conclusion, this study maintains that prioritizing questions related to the business in the process of strategic decision-making, considering external factors, resources and internal capacities, as well as addressing aspects related to ownership and the type of family involvement in the business, are fundamental elements for the insertion and success of a family company in a foreign market. The support of external agents is also shown as an important element in defining an international culture